FRI0526 Long-Term Efficacy of IL-1 Blockers in Papa Patients. (9th June 2015) - Finetti, M.; Caorsi, R.; Marotto, D.; Buoncompagni, A.; Omenetti, A.; Lattanzi, B.; Minoia, F.; Picco, P.; Jorini, M.; Martini, A.; Gattorno, M.
Abstract : Background: PAPA syndrome (Pyogenic Arthritis, Pyoderma gangrenosum, and Acne) is an ultra-rare autosomal dominant, auto-inflammatory disease associated to mutations in the PSTPIP1 / CD2BP1 gene. The therapeutic approach during recurrences consists of steroids, while no agreement exists on the chronic management. Evidences on the use of biologics are anecdotal and variable results have been reported. Objectives: To evaluate the long-term response to treatment with IL1 antagonist in six patients affected by PAPA syndrome. Methods: Six patients (M:F=3:3; 4 pediatric, 1 young adult and 1 adult, mean age 18 years, range 3-50) affected by PAPA syndrome were enrolled and treated with IL1 blockers (5 patients Anakinra, 1 patient Anakinra followed by Canakinumab). Three patients were already treated with anti-TNFα monoclonal antibodies without benefit. Data were collected retrospectively (mean follow-up 26 months, range 4-38). The frequency of articular and cutaneous flares in the 24 months before starting therapy where compared to those occurred during anti-IL1 regimen. Acute phase reactants (ESR, CRP, SAA) were assessed at the last visit before the study enrolment and at last follow-up. Results: All the patients displayed a significant decrease in frequency of disease flares (Table ) and normalization of acute phase reactants. Three patients were asymptomatic during whole follow-up. Patient#4, with a severe and persistent pyoderma gangrenosum, displayed a partial response to Anakinra partially due to a poor compliance to daily s.c. administration. The shift to Canakinumab lead to a fast and complete resolution of the skin manifestations. Conclusions: The long-term use of IL1 blockers is associated to satisfactory and persistent control of clinical manifestations and laboratory findings in PAPA syndrome. Disclosure of Interest: M. Finetti: None declared, R. Caorsi: None declared, D. Marotto: None declared, A. Buoncompagni: None declared, A. Omenetti: None declared, B. Lattanzi: None declared, F. Minoia: None declared, P. Picco: None declared, M. Jorini: None declared, A. Martini Grant/research support from: Unrestricted grants from SOBI and Novartis, Speakers bureau: Speaker's fees, M. Gattorno Grant/research support from: Unrestricted grants from SOBI and Novartis, Speakers bureau: Speaker's fees